1994
DOI: 10.1037/0033-295x.101.4.676
|View full text |Cite
|
Sign up to set email alerts
|

The lexical nature of syntactic ambiguity resolution.

Abstract: Ambiguity resolution is a central problem in language comprehension. Lexical and syntactic ambiguities are standardly assumed to involve different types of knowledge representations and be resolved by different mechanisms. An alternative account is provided in which both types of ambiguity derive from aspects of lexical representation and are resolved by the same processing mechanisms. Reinterpreting syntactic ambiguity resolution as a form of lexical ambiguity resolution obviates the need for special parsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

95
1,398
7
21

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,818 publications
(1,521 citation statements)
references
References 120 publications
(275 reference statements)
95
1,398
7
21
Order By: Relevance
“…We found that verb-bound preferences indeed influence syntactic processing: there was an inverse preference effect of syntactic priming effects in response choices and a positive preference effect of syntactic priming effects in response latencies. This support the idea that syntactic processing is lexically guided (lexicalist parsing models of syntax; e.g., Jackendoff, 2002;Joshi & Schabes, 1997;MacDonald et al, 1994).…”
Section: Discussionsupporting
confidence: 76%
“…We found that verb-bound preferences indeed influence syntactic processing: there was an inverse preference effect of syntactic priming effects in response choices and a positive preference effect of syntactic priming effects in response latencies. This support the idea that syntactic processing is lexically guided (lexicalist parsing models of syntax; e.g., Jackendoff, 2002;Joshi & Schabes, 1997;MacDonald et al, 1994).…”
Section: Discussionsupporting
confidence: 76%
“…However, as laid out in the introduction, real language use is not a random affair solely constrained by uncoupled sets of grammatical rules. Different layers of the grammar are tightly linked to each other through the lexicon, as well as through correlated constraints (MacDonald et al, 1994;Tanenhaus & Trueswell, 1995) or interface rules (Jackendoff, 2002) that express mappings at a supralexical level. In addition, the interpretive layer is strongly correlated to the real world outside the language system.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, at least previously proposed "single-mechanism" models of grammatical and lexical phenomena (Bates and MacWhinney, 1989; Joanisse and Seidenberg, 1999;MacDonald et al, 1994;Rumelhart and McClelland, 1986) do not appear to be compatible with the PDH, or with the grammatical/lexical dissociations found in SLI (see Pinker and Ullman, 2002a;Ullman and Gopnik, 1999;van der Lely and Ullman, 2001). However, it must be noted that the single-mechanism 43 (connectionist) computational perspective is not in principle incompatible with the PDH and the findings described above, since distinct declarative and procedural systems can and have been modeled by connectionist simulations (Dominey et al, 2003;McClelland et al, 1995).…”
Section: Conclusion 41mentioning
confidence: 95%
“…The PDH is largely motivated by the Declarative/Procedural model of language, and evidence supporting the PDH also supports this perspective. The PDH predicts that SLI is associated with non-linguistic functions that are subserved by the same brain system that also underlies grammar; this outcome is clearly not expected by the view that domain-specific modules subserve distinct aspects of grammar (Chomsky, 1995;Fodor, 1983;Frazier and Fodor, 1978;Grodzinsky, 2000).Likewise, at least previously proposed "single-mechanism" models of grammatical and lexical phenomena (Bates and MacWhinney, 1989; Joanisse and Seidenberg, 1999;MacDonald et al, 1994;Rumelhart and McClelland, 1986) do not appear to be compatible with the PDH, or with the grammatical/lexical dissociations found in SLI (see Pinker and Ullman, 2002a;Ullman and Gopnik, 1999;van der Lely and Ullman, 2001). However, it must be noted that the single-mechanism 43 (connectionist) computational perspective is not in principle incompatible with the PDH and the findings described above, since distinct declarative and procedural systems can and have been modeled by connectionist simulations (Dominey et al, 2003;McClelland et al, 1995).…”
mentioning
confidence: 95%